THE INFLUENCE OF DEBT DEFAULT, COMPANY SIZE, AND OPINION SHOPPING ON RECEIVING GOING CONCERN OPINIONS - Lego Waspodo (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This study aims to examine the effect of debt default, company size and opinion shopping to the acceptance of going concern audit opinion. The population in this study are all of the property, real estate, and building construction companies that are listed on the Indonesia Stock Exchange. The sampling method used in this research was purposive sampling, so 83 company samples were obtained for four years (2019-2022). The data were analyzed using descriptive statistics and logistic regression. The results of this study indicate that: (1) debt default has a positive effect on the acceptance of going concern audit opinion; (2) company size has negative effect on the acceptance of going concern audit opinion; (3) opinion shopping has a positive effect on the acceptance of going concern audit opinion.